Odpowiedzi

2009-11-07T23:56:45+01:00
A) -2(x-1)3-(x+2)(x2-3)
-6x+6-(x^3+2x^2-3x-6)
-x^3-2x^2-3x+12

b) -(x+1)2-x(x+2)
-2x-2-x^2-2x
-x^2-4x-2

c) -(x+2)3-(x-1)(x+1)
-3x-6-x^2+1
-x^2-3x+1

d) 2(x+1)3-(x+1)(x+1)2
6x+6-2x^2+4x-2
-2x^2+10x+4
-2(x^2+5x+2)

e) -(3-x)3-(x-2)2+(x+1)

-9+3x-2x+4+x+1
2x-4
2(x-2)
2009-11-07T23:59:56+01:00
A) -2(x-1)3-(x+2)(x2-3) = -6x +3 -x3+3x-2x2+6 = -3x+9-x3-2x2
b) -(x+1)2-x(x+2) = -2x-2-x2-2x = -4x-2-x2
c) -(x+2)3-(x-1)(x+1) = -3x-6 -x2+1
d) 2(x+1)3-(x+1)(x+1)2 = 3x+3-x2+2x+1 = 5x +4 -x2
e) -(3-x)3-(x-2)2+(x+1) = -9+3x-2x+4+x+1 = -4+2x
2009-11-08T00:15:13+01:00
-2(x-1)³-(x+2)(x²-3)=-2(x³-3x²+3x+1)-(x³-3x+2x²-6)=-2x³+6x²-6x-2-x³+3x-2x²+6=-3x³+4x²-3x+4

b) -(x+1)²-x(x+2)=-(x²+2x+1)-x²-2x=-x²-2x-1-x²-2x=-2x²-4x-1

c) -(x+2)³-(x-1)(x+1)=-(x³+6x²+12x+4)-(x²-1)=-x³-6x²-12x-4-x²+1=x³-7x²-12x+1

d) 2(x+1)³-(x+1)(x+1)²=2(x³+3x²+3x+1)-x³-3x²-3x-1=
=2x³+6x²+6x+2-x³-3x²-3x-1=x³+3x²+3x+1

e) -(3-x)³(x-2)²+(x+1)=-(27-27x+9x²-x³)(x²-4x+4)+x+1=
=-27x²+108x-108+27x³-108x²+108x-9x⁴+36x³-36x²+4x⁴+4x³+x+1=
=x⁵-5x⁴+67x³-171x²+217x-107